(x+2y)dx-xdy=0

Simple and best practice solution for (x+2y)dx-xdy=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+2y)dx-xdy=0 equation:


Simplifying
(x + 2y) * dx + -1xdy = 0

Reorder the terms for easier multiplication:
dx(x + 2y) + -1xdy = 0
(x * dx + 2y * dx) + -1xdy = 0

Reorder the terms:
(2dxy + dx2) + -1xdy = 0
(2dxy + dx2) + -1xdy = 0

Reorder the terms:
2dxy + -1dxy + dx2 = 0

Combine like terms: 2dxy + -1dxy = 1dxy
1dxy + dx2 = 0

Solving
1dxy + dx2 = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Factor out the Greatest Common Factor (GCF), 'dx'.
dx(y + x) = 0

Subproblem 1

Set the factor 'dx' equal to zero and attempt to solve: Simplifying dx = 0 Solving dx = 0 Move all terms containing d to the left, all other terms to the right. Simplifying dx = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(y + x)' equal to zero and attempt to solve: Simplifying y + x = 0 Reorder the terms: x + y = 0 Solving x + y = 0 Move all terms containing d to the left, all other terms to the right. Add '-1x' to each side of the equation. x + -1x + y = 0 + -1x Combine like terms: x + -1x = 0 0 + y = 0 + -1x y = 0 + -1x Remove the zero: y = -1x Add '-1y' to each side of the equation. y + -1y = -1x + -1y Combine like terms: y + -1y = 0 0 = -1x + -1y Simplifying 0 = -1x + -1y The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| x(x-4)=2 | | -10z-2=-z+7 | | r^2+24r+169=0 | | 2p^2=-18p | | 4d^2+15d-4= | | 5+8(x-2)=(3x+1)4+1 | | Y=5/2x-5 | | 4/(1-x)=5/(1+x) | | c^2-9c= | | 13/(2x-3)=11(x+3) | | 13/2x-3=11x+3 | | -15t^2+60t+10=0 | | 4x-2.1=-6.3+1.9x | | 3x^2+4x-17=0 | | (x+1/x)^2-5(x+1/x)+6=0 | | 5/6x+1+3 | | 3j-7j=12 | | (x-9)(5x+12)=0 | | 121=r^2 | | 625=r^2 | | 324=r^2 | | 2x+5=3+5x | | 6-5=4x+1 | | 6x+5=4x+1 | | 5805.86=3.14r^2 | | 4j-9j+3=-3 | | (x-7)(y-5)= | | (5x)=(3x+28) | | (3x-1)(3-8x)= | | y=4(7x+100) | | y=1/2+5(0,3) | | (8k-9)(3k-7)= |

Equations solver categories